2014
DOI: 10.1007/s10646-014-1341-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietborne cadmium on life history and secondary production of a tropical freshwater cladoceran

Abstract: The presence of metals in aquatic environments has increased worldwide. Environmental assessments of metals in freshwater ecosystems presume that toxicity is mainly caused by aqueous exposure, but dietborne exposure (contaminated food) in zooplankton may occur because microalgae carry metal ions through adsorption/absorption of dissolved metal species, resulting in toxic effects once ingested by the animals. However, official regulations for ecotoxicological assays in most countries do not consider the toxic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…The fuels and lubricating oils used in this port have high concentrations of metals, namely Cd, Cr, Cu, Mn, Ni, Pb, and Zn (Pulles et al, 2012;Coufalík et al, 2019). Studies on the presence of these metals in domestic wastewater (Souza et al, 2014;Thewes et al, 2011) support the role of wastewater emissions in metal pollution in the aquatic environment.…”
Section: Characterization Of Water Quality Through Physicochemical An...mentioning
confidence: 90%
See 1 more Smart Citation
“…The fuels and lubricating oils used in this port have high concentrations of metals, namely Cd, Cr, Cu, Mn, Ni, Pb, and Zn (Pulles et al, 2012;Coufalík et al, 2019). Studies on the presence of these metals in domestic wastewater (Souza et al, 2014;Thewes et al, 2011) support the role of wastewater emissions in metal pollution in the aquatic environment.…”
Section: Characterization Of Water Quality Through Physicochemical An...mentioning
confidence: 90%
“…The increasing accumulation of exogenous substances in estuarine areas has negatively affected their biota and led to ecosystem imbalance (Pimentel et al, 2016). In addition, toxic compounds can bioaccumulate and be transferred through the food chain (Souza et al, 2014), posing a risk to human health (Rabaoui et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, podem-se elencar alguns fatores críticos associados à disposição inadequada dos REEE, os quais favorecem a exposição da população aos agentes tóxicos dos REEE: (Ipea, 2013). Há evidências de que catadores e atores intermediários (sucateiros) coletam REEE no Brasil (Ongondo; Williams; Cherrett, 2011), e que alguns praticam a dissolução de Placas de Circuito Impresso (PCI) com ácido, bem como a queima de cabos e componentes, para a separação de metais (Lundgren, 2012;Souza, 2014).…”
Section: Destinação Inadequada Dos Reeeunclassified
“…Uma grande parte dos REEE no Brasil segue uma cadeia composta por atores informais, que atuam nos processos de coleta e comercialização de aparelhos e de suas partes, e que muitas vezes estão submetidos a atividades insalubres para obtenção de materiais valiosos, de forma rudimentar. Dentre os processos mais comuns identificados nas cadeias informais estão a queima de componentes para a separação de metais, e a dissolução de PCI com ácido para a obtenção de metais raros, presentes nas suas superfícies (Lundgren, 2012;Souza, 2014). Esses processos expõem os trabalhadores informais e comunidades próximas a fumaças e líquidos extremamente tóxicos, que podem causar desde problemas respiratórios a câncer e doenças neurológicas e cardíacas (Lundgren, 2012).…”
Section: Destinação Inadequada Dos Reeeunclassified
“…While research on the accumulation and effects of metals in shell sh has traditionally focused primarily on the exposure pathway in dissolved form, researches have shown that the dietary exposure pathway can be critical and sometimes dominant (Tang et al 2011;Wang 2013). Studies that address this aspect of toxicity have been increasingly reported in the literature for copper (Rodgher et al 2009;Gusso-Choueri et al 2012;Rocha et al 2016), cadmium (Barata et al 2002;Rodgher and Espíndola 2008a;Souza et al 2014), zinc (De Schamphelaere et al 2004;Rodgher et al 2020). They are essential for understanding the trophic transfer of these elements in ecosystems.…”
Section: Introductionmentioning
confidence: 99%